Epidemiological profile of elderly diabetic patients admitted to a University Hospital in western Paraná (International Seven Journal of Health Research, 2024)
Introduction: Diabetes is a metabolic condition characterized by hyperglycemia due to issues in insulin secretion or action. Objectives: To identify the prevalence of diabetes in the elderly population, characterizing the patterns of disease occurrence and investigating possible gender and age disparities as well as the influence of sociodemographic factors and comorbidities. Methodology: A retrospective longitudinal observational study in which data from patients with diabetes mellitus hospitalized at a University Hospital in Western Paraná from 2015 to 2022 were analyzed. Results: The results revealed a significant prevalence of diabetes, with the majority of patients being male and presenting a sociodemographic profile characterized by married individuals, of white ethnicity, and Catholic religion. The main causes of hospitalizations were urinary tract sepsis, urinary tract infection, and pulmonary sepsis, while arterial hypertension was the most prevalent comorbidity. Hospital evolution showed that most patients were discharged, with a significant proportion of deaths. Conclusion: The importance of a multidisciplinary and individualized approach in managing diabetes in the elderly is emphasized, along with the need to consider contextual and population factors in interpreting epidemiological data.